High Correlation of Visual Inspection and a Smartphone-Based Electronic Reader of Two Dual Rapid Diagnostic HIV/Syphilis Assays. (4th October 2017) - Allan-Blitz, Lao-Tzu; Rivera, Silver Vargas; Konda, Kelika; De Cortina, Sasha Herbst; Caceres, Carlos; Klausner, Jeffrey
Abstract: Background: The HRDR-200 automated reader (Cellmic, LLC, CA, USA) is an opto-mechanical smartphone attachment that reads lateral flow-based rapid HIV/Syphilis combo assays. The reader may minimize human errors in interpreting rapid tests as well as provide a centralized data system for epidemiologic monitoring. Methods: We enrolled men who have sex with men and transgender women >18 years old seeking services at a sexually transmitted disease clinic in Lima between October 2016 and April 2017. Venous blood was tested using two dual HIV and Syphilis rapid tests (SD BIOLINE HIV/Syphilis Duo (SD), Republic of Korea; and First Response HIV 1 + 2/Syphilis Combo (FR), India). HIV infection was confirmed with fourth-generation EIA tests, while Syphilis was confirmed with RPR, TPPA, and TPHA titers. Clinic staff visually inspected rapid tests, after which the tests were read by the HRDR-200. To assess how well the reader results correlated with visual inspection we calculated negative and positive percent agreement, concordance, and kappa statistic. Results: Of 283 participants, 34% were HIV-infected and 46% had treponemal antibodies (69% of whom had reactive RPR titers). The concordance of reader results with visual inspection was high for both antibodies and both rapid assays (see Table). Conclusion: Given the high correlation of the reader with visual inspection, further investigation is warranted into the potential utility of the reader for epidemiologic monitoring as well as for improving HIV and Syphilis diagnosis in areas without technicians trained in visual inspection of rapid tests. Disclosures: All authors: No reported disclosures.